PM SHRI Transforming India’s Education Landscape through Excellence and Innovation - SINHA, SHARAD; SINGH, ABHISHEK (JOURNAL OF INDIAN EDUCATION, 2025)
Indian education system is evolving throughout its journey since independence. Over the period, landmark initiatives taken up by the Government become the benchmark for many developing countries. However, some issues and challenges still persists that need to be addressed. The paper critically examines the existing structure of India’s education system, focusing on its key challenge to achieve equitable and quality education. Constraints that hamper effective functioning and achievement of desired outcomes, such as inadequate infrastructure, teacher shortage, outdated curricula, rote learning methods and regional disparities in access to education are explored in detail. Despite continuous efforts to reform the system taken up from time-to-time, like policy interventions and expansion of educational coverage, many challenges persist, particularly in ensuring student engagement, fostering critical thinking and bridging the digital divide. This paper aims to understand the systemic bottlenecks that hindered the holistic development of students, and hastened the progress toward achieving desired goals and targeted outcomes. While the need for comprehensive reforms, which paved the way for new policy frameworks like the National Education Policy (NEP) 2020 and the path breaking initiative like PM SHRI (Pradhan Mantri Schools for Rising India) standing up to the challenges posed in 21st century challenges, such as infrastructure gaps, digital divides, and disparities in learning outcomes across rural and urban areas. This paper highlights how PM SHRI schools are set to redefine the learning experience through modern pedagogical approaches, eco-friendly infrastructure and a stronger emphasis on foundational literacy and numeracy skills. Additionally, the paper evaluates the programme’s potential to foster holistic development, integrate skill-based education and promote equity by enhancing access to quality education for underserved communities aligning with the national goals of the New Education Policy (NEP) 2020